Displaying Mr Selfridge - Cruz-Rus, Celia (My University, 2015)
Whereas, in literature a stream of recent bio-fictions have focused their efforts on resurrecting great Edwardian authors, the first season of Mr Selfridge (2013), based on Lindy Woodhead’s biography Shopping, Seduction & Mr Selfridge (2007), features a capitalist hero and constitutes an intriguing object of study which connects the present context with the history of England and of costume drama itself. Consequently, this paper will analyse the series in terms of how it relates to and differs from other representations of Edwardian characters, in an attempt to explore what the impulse lying behind Mr Selfridge’s filmic return could be.
Keywords: Cine; Biografía; Biopic; Neo-Edwardian; Shopping; Film studies; Literature